Partial influence of leadership variables on Middle Managers of foreign capital companies in Tangerang - Chaidar, Diar Fachmi Rachmat (PT Aksara Indo Rajawali, 2022)
Business turnover is greatly influenced by leadership. If a leader does not understand how to manage a company, it will have a negative impact on the company itself. Therefore, this research will investigate how leadership variables have a partial impact on middle managers in foreign capital companies in Tangerang. Quantitative descriptive is used to collect data. The research results show that leadership must devote all their attention and continuously strive to help and support employee success. As leaders, superiors understand various new strategies that are useful for achieving big company goals. So, the leadership variable influences the company's Middle Manager partially, both directly and indirectly.